Artificial Intelligence-Driven Digital Communication : Evaluating the Mobile-Applications and Fostering Policies for Cultural Heritage Preservation - Sajida Sajida; Sekar Arum Nuswantari; Suprapti Suprapti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates whether AI is a possible game-changer in the communications industry for cultural manifestations digitally and, hence, an active protagonist in the moisture preservation and sustenance of Nusantara cultural heritage. By examining eight cultural applications on the Google Playstore ranging from cultural education application to local language dictionary application and so on, this research evaluate the existing mobile apps and future opportunities for integrating AI into cultural preservation endeavors. The results indicate that present applications do not employ AI but there is great potential for incorporating AI features such as adaptive learning, semantic search, and personalization of content recommendations. The study stresses having a solid digital backbone defined by an inclusive policy framework and collaborative inter-disciplines which is crucial because of challenges such as disparities in technological access, data privacy concerns, and resistance from culture. Policy recommendations ensuring the responsible use of AI are put forward in terms of ethical standards, digital literacy, and sustainable development that strive to advance Indonesia's digitalization narratives in harmony with cultural sustainability in the wake of the digital era.